Study of Degradation of Polycyclic Aromatic Hydrocarbons (PAHs) in Sureat Lake Water using Hydrodynamic Cavitation - هيثم شاهين; حسين جنيدي; أحمد قره علي; امال عطيه (Latakia University Journal -Engineering Sciences Series, 2022)
In this research, the effect of changing the size and number of holes for six orifice plates was studied to evaluate the effectiveness of hydrodynamic cavitation in the degradation of polycyclic aromatic hydrocarbons (PAHs) in Sureat Lake water. A constant inlet pressure was applied and the degradation rate constant was determined for each plate after operating times (5, 10, 15, 20, 25 and 30 min). The results showed the effectiveness of hydrodynamic cavitation in removing (PAHs), the orifice plate (6) was the best efficient, as the removal percentage reached 100% at time = 20 min, the degradation rate constant was 6 * 10 -3 sec-1, and the cavitational yield was 6 * 10-9 ng/ j. Therefore, plate (6) can be considered the best economic and environmental choice to obtain the largest percentage of PAHs removal.